(untitled) - Falwell, Jerry (Grand Rapids, MI, U.S.A, 1983)
This volume contains twenty-five of the finest and most blessed sermons from of God's choicest servants from the past. Though these preachers represent a wide range of denominational backgrounds, each was greatly used of God to influence his own generation. They are: Johnathan Edwards, George Whitefield, John Wesley, William Carey, Christmas Evans, Robert Murray McCheyne, Charles G. Finney, Charles Haddon Spurgeon, D. L Moody, Joseph Parker, T. DeWitt Talmage, Sam Jones, Alexander Maclaren, B. H. Carroll, J. Wilbur Chapman, R. A. Torrey, F. B. Meyer, Billy Sunday.
English
Keywords: Christian sermons